Financial Management of MSMEs: Cost Control Strategies and Profit Improvement Amid Economic Uncertainty - Subranta, Aris; Sari, Gema Ika; Dzikri, Ahlu (Ilomata International Journal of Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, yet they remain vulnerable to economic uncertainty caused by global crises, supply chain disruptions, and policy shifts. These challenges emphasize the need for effective financial management strategies to ensure sustainability and profitability. This study aims to identify cost control strategies, evaluate the role of digital innovation and business model adaptation in profit improvement, and propose a holistic financial management framework for MSMEs. Using a qualitative approach with a literature review design, data were collected from scholarly journals, research reports, and policy documents published in the last five years, supported by relevant classical works. Content analysis was applied to identify patterns and relationships among financial practices, cost efficiency, and profit sustainability. The findings reveal that cost discipline, including zero-based budgeting, inventory optimization, and supplier negotiations, is critical for maintaining liquidity and operational efficiency during crises. At the same time, digital innovation—through e-commerce, QRIS-based payments, and cloud accounting—reduces transaction costs and expands market reach, while business model adaptation ensures income diversification and resilience. Importantly, financial literacy among MSME owners strengthens the integration of these strategies, enabling them to respond adaptively to uncertainty. The study concludes that a holistic model combining cost control, digital transformation, and reinvestment in financial and human capital offers MSMEs a sustainable pathway to resilience and long-term profitability.